Pengaruh Bantuan Sosial Program Keluarga Harapan (PKH) terhadap Tingkat Penurunan Kemiskinan Masyarakat Penerima Manfaat di Desa Pendem - Rohma Nur Anisa; Amin Yusuf; Yudi Siswanto (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2025)
Poverty remains a major issue faced by developing countries, including Indonesia. To address this problem, the government launched the Program Keluarga Harapan (PKH) as a conditional social assistance initiative targeted at low-income families. This study aims to analyze the influence of PKH on reducing poverty levels in Pendem Village, Karanganyar Regency. The research employed a quantitative method with a correlational approach. A total of 147 respondents were selected using a simple random sampling technique. The analysis results show that PKH has a positive and significant effect on poverty reduction, with a significance value of 0.000 < 0.05 and an R Square value of 0.354, indicating that the PKH variable explains 35.4% of the variation in poverty reduction. These findings suggest that PKH makes a real contribution to meeting basic needs, reducing economic burdens, and improving the welfare of poor communities. However, the effectiveness of PKH does not stand alone, as other factors such as education, employment opportunities, and access to basic services also influence poverty. Therefore, integration of PKH with other community empowerment programs is needed to ensure more sustainable impacts. The analytical technique used in this study is simple linear regression